Case reportCoronary artery aneurysm in a two-year-old child - Nisli, Kemal; Sayin, Omer A.; Goker, Burcu; Dindar, Aygun; Tireli, Emin; Dayioglu, Enver (Archives of Medical Science, 2008)
Kawasaki disease is an acute vasculitis affecting predominantly children. The disease leads to coronary artery ectasia and damage which further result in ischaemic heart disease, being the most common cause of myocardial infarction in childhood. The aetiology and guidelines for the definitive diagnosis are still not identified clearly and the aim of current treatment strategies is to reduce inflammation and prevent ischaemic myocardial damage. In this report, we present the perioperative cardiac images of a two-year-old boy who had giant coronary arteries. He was admitted with the diagnosis of fibrinous pericardial effusion and was referred for pericardiectomy. During surgery we found ectatic coronary arteries.